Chiral Nanostructured Bimetallic Au–Ag Films for Enantiomeric Discrimination. Issue 19 (29th May 2022) - Yang, Pu; Deng, Quanzheng; Duan, Yingying; Liu, Zexi; Fang, Yuxi; Han, Lu; Che, Shunai
Abstract: Herein, the chiral nanostructured bimetallic Au–Ag films (CNAAFs) with both photomagnetic‐chiral anisotropy to enantiomers (PM‐ChAC‐E ) and surface‐enhanced Raman scattering‐chiral anisotropy to enantiomers (SERS‐ChAC‐E ) for efficient enantiomeric discrimination are reported. The CNAAFs are synthesized by electrodeposition on n ‐type Si (n‐Si) substrates with the assistance of N ‐acetyl‐L/D‐cysteine (S/R‐NAC) as symmetry‐breaking agents, which are consisted of polycrystalline Boerdijk–Coxeter–Bernal (BCB) tetrahelical structured Au–Ag alloy nanowires grown on n‐Si substrates perpendicularly. The anisotropic factors of PM‐ChAC‐E ( g PM‐ChA ) and SERS‐ChAC‐E ( g SERS‐ChA ) of CNAAFs in the range of 0.68–1.12 and 1.45–1.89 are obtained, respectively. Considering the increase of magnetic fields and SERS intensities with enantiomeric excess ( ee ) values of adsorbed enantiomers on the CNAAFs are higher than that of pure chiral nanostructure Au films, the enhancement of PM‐ChAC‐E and SERS‐ChAC‐E effects of CNAAFs can be attributed to the enhanced selective spin polarization coupling between CNAAFs and enantiomers. It is predicted to be due to the strong surface plasmon resonance generated by the active electrons of Ag under laser irradiation. Abstract : Antipodal chiral nanostructured bimetallic Au–Ag films as effective chiral platforms are electrodeposited on n ‐type Si substrate in the presence of S/R‐NAC as symmetry‐breaking agents with both enhanced PM‐ChAC‐E and SERS‐ChAC‐E effect for efficient enantiomeric discrimination.